Leakage and Flashover Current in the provided Silicon Rubber Coal Dust Pollution (Fly Ash) - Maulana, Muhammad Bintang; Kurnia, Rizda Fitri; Fitria, Syarifa; Nawawi, Zainuddin (Program Pascasarjana Universitas Sriwijaya, 2024)
This research study on leakage and flashover currents in silicone rubber treated with coal dust (fly ash) pollutants with variations in the duration of impurity conditioning within 1, 2, 3 days, and no conditioning. This research prepares for testing the RTV 497 silicone rubber test sample which is formed into a sheet with a thickness of 1 mm while the length and width are 50 x 25 mm which is attached with a leaf-like sample electrode system which is designed using the sketch up application with the number of samples of each 5 pieces each for each variation of conditioning carried out, then tested using an Aluminum Tape electrode system with a gap between the Aluminum Tape electrodes of 5 mm. To determine the value of the leakage current that passes through the surface of the Silicone Rubber, voltages of 220 V, 500 V, and 1000 V are applied, left for 1 minute for each voltage application variation to read the value of the current flowing on the sample surface, then the voltage is increased slowly until flashover occurs. The test results showed a leakage current value of 1, 2, and 3 days without conditioning when applying a voltage of 220 V is 34.53; 34.69; 34.81; and 35.09 mA, the same for application at a voltage of 500; and 1000 V that is the leakage current value increases. This is for any current flowing from the conductor to the ground to pass through the outer surface of the insulator. If the surface of the insulator has a layer of contaminants, it can affect the leakage current that flows on the surface. Meanwhile, the flashover test results with the same sample obtained a value of 4112.8; 3819.4; 3676.4; and 3511 V, the data obtained is that the voltage decreases with the longer the conditioning time is carried out since dust contaminants tend to settle and stick to the insulator, which is one of the biggest causes of flashover and failure.